Desenvolvimento de uma câmara de combustão para combustíveis a base de metano em motores de ignição por centelha - Silva, Cristian Douglas Rosa da (2024)
The increasing demand for alternative and sustainable fuels is driving research into technologies that enhance engine efficiency and reduce pollutant emissions and greenhouse gases. Biogas, derived from biomass, stands out as a viable option within the Brazilian energy matrix. This study aims to analyze and develop a more suitable piston geometry for a spark-ignition engine running on methane-based fuels, focusing on maximizing thermal efficiency and minimizing emissions, compared to the original Diesel engine geometry. The primary objective is to improve the burn rate to approach the ideal cycle, promoting a sustainable alternative to diesel for freight transport. Combustion optimization can be achieved by adjusting piston geometry, considering parameters such as bowl shape, crevices, surface-to-volume ratio, compression ratio, Squish area, and height, which increase thermal efficiency and reduce emissions. The research was conducted at the UFSM's Group of Research in Engines, Fuels, and Emissions, using a modified Hyundai HR 2.5L engine to operate in the Otto cycle with natural gas. The engine was installed on a dynamometer for stationary tests. CFD simulations were performed using CONVERGE software, adjusting parameters like compression ratio and Squish area. The pistons' geometries were modeled in SolidWorks and simulated to assess combustion and turbulence parameters, with some geometries fabricated and tested experimentally. The results show that a higher compression ratio increase indicated efficiency without significantly impacting turbulence. On the other hand, the Squish area has a substantial influence on turbulence and the mean flow velocity near the spark plug. However, increasing the Squish area also increases the surface-to-volume ratio, leading to higher heat transfer losses. Experimentally, the higher turbulence intensity and flow velocity in the combustion chamber improved the burn rate, reduced combustion duration, and enhanced stability, leading to lower ISCO and ISTHC emissions. However, NOx emissions increased due to higher combustion temperatures and greater air mass per cycle, attributed to the lower compression ratio. Under supercharging conditions, the proposed piston demonstrated greater operational robustness, operating in a controlled manner and minimizing autoignition due to the shorter combustion durations and lower compression ratio.